The Radial Velocity of OGLE-2015-BLG-0966S. (2nd June 2017) - Johnson, Samson A.; Yee, Jennifer C.
Abstract: The distance to the planetary system OGLE-2015-BLG-0966L and the separation between the planet and its host star are ambiguous due to an ambiguity in the distance to the source star. We attempt to break this degeneracy by measuring the systemic radial velocity of the source star measured from a spectrum taken while the source was highly magnified. Our measurement of v LSR = 54.2 ± 0.3 km s − 1 does not definitively resolve the nature of the source, but supports the general conclusion that the source is in the bulge. This work demonstrates that even a low signal-to-noise spectrum has the potential to provide useful information for characterizing microlensing source stars.